Analisis Perkembangan Indeks Harga Konsumen di Kota Medan - Sari Wulandari; Muhammad Dani Habra (COSTING : Journal of Economic, Business and Accounting, 2020)
The Consumer Price Index (CPI) is one of the important economic indicators that can provide information about the development of prices of goods and services (commodities) paid by consumers or the public especially the city community. This study aims to analyze the Development of the Consumer Price Index in Medan City. The benefits of this research are a description of the fluctuations in commodity prices for basic needs of the community at the level of consumers or retail traders. This type of research is descriptive qualitative. The subject in this study is the Central Statistics Agency and the object in this study is the Consumer Price Index through seven groups of household expenditure in 2018-2019. The results showed that the development of price indices in Medan City tends to fluctuate from seven types of household expenditure groups. During the January-December 2019 period the highest inflation of the seven types of expenditure was foodstuffs. Keywords: Consumer Price Index, Inflation Rate